Verified Signal Processing Algorithms in MATLAB and C Advised by Israel Greiss - Dickman, Arie.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book is written for engineers who need to develop algorithms used for signal processing and/or implement algorithms using the C programming language or MATLAB. The book features a rich collection of recipes for applied signal processing such as FIR, IIR, FFT, correlation, complex FIR, adaptive filters and others. The book applies to those who want to implement in the shortest time to market working systems that are built from a collection of building blocks implemented in an FPGA firmware or C language software, running on an SBC or DSP. Structured as an instantly applicable guide, the author covers a wide collection of required solutions to common encountered problems with a software guide. All Codes in the book are verified and processing times for all C codes are specified, enabling the reader to estimate processing time on his own target, by comparing it to the I5 2.9 GHz CPU used here. Endorsements: Your book bridges a gap between theory and implementation on hardware - which is a topic relevant to many in industry and many students who are targeting the digital signal processing industry (including communications and robotics) Professor Alfred Hero, University of Michigan, Ann Arbor, USA I believe you that for many engineers the book will be practical Professor Anthony J. Weiss, Tel Aviv University, Israel.
1-Overview of signal detection -- 2-Measures for verification and implementation of algorithms -- 3-Narrow band & wide band processing basics -- 4-Complex Finite Impulse Response filters -- 5-Infinite Impulse Response filters -- 6-Non linear and batch filters -- 7-Interpolators -- 8-Direct digital synthesis -- 9-Inverse Fast Fourier Transform -- 10-Hilbert transform -- 11-Channelizer -- 12-Correlation -- 13-Adaptive filters -- 14-Unequally spaced sampling -- 15-Encountered problems in Signal Processing & solutions.
Keywords: Signal processing; Telecommunication; Electronic circuits; Digital and Analog Signal Processing; Communications Engineering, Networks; Electronic Circuits and Systems; Signal processing -- Digital techniques -- Data processing; C (Computer program language); MATLAB